Primary-Secondary Wavelengths Spectrophotometric Determination of Fluoride in Environmental Water - Gao, Hong-Weng; Zhang, Zhi-Wen (Asian Journal of Chemistry, 2012)
In the presence of lanthanum nitrite the reaction between and alizarine complexan at pH 4.1 was applied for the improvement of the determination of trace amounts of fluoride in environmental water by primary-secondary wavelengths spectrophotometry (PSWS). Results showed that the recovery of fluoride was between 97.4 and 109% and the relative standard deviation less than 3.1% for the analysis of dour water samples. In addition, the detection limit of fluoride was only 0.01 mg/L by PSWS which was one-fifth of that obtained by ordinary spectrophotometry.